Secularities-in-Practice: Accommodating Muslim Pupils and Preserving Danish Identity in Multi-ethnic Danish Schools - Gilliam, Laura (Journal of religion in Europe, 2019)
This article explores the ideals and practices of moderate secularism characteristic of Danish schools' approach to Muslim pupils, Islam, and religion in general. It argues that while these reflect the Danish culture of secularity' (Wohlrab-Sahr & Burchardt 2012), differences in secularities-in-practice' between schools necessitate a look at the interactional level and institutional context. Drawing on Norbert Elias' figurational sociology, the article shows how an increase in Muslim pupils changes the webs of interdependencies in the social figuration of teachers, children, and parents in Danish schools and how the schools attempt to maintain institutional practices, civilised interaction, and a Danish identity.